Hygienic Monitoring of Working Area Air Pollution by Particulate Matter of ticagrelator in the Pharmaceutical Factory - I. A. Pozharnov; A. S. Simakov; N. A. Shulga; A. Yu. Savchenko; O. I. Perederyaev; L. S. Synkova; Yu. V. Medvedev; E. N. Fisher (Разработка и регистрация лекарственных средств)
Introduction. Hygienic monitoring of air pollution at the pharmaceutical enterprise required by the law of the Russian Federation (orders, standards, methodological guidelines and guidelines). This requirement follows from the need to protect the personnel of the pharmaceutical plant from the adverse air conditions of the working area, which may contain suspended solids of active pharmaceutical ingredient (API). Despite the use of breathing equipment by staff and occupational safety requirements, the risk to workers should be minimized by regular assessment of air pollution.Aim. The purpose of the stady is to carry out hygienic monitoring of working area air tikagrelor – API of the medicinal preparation Brilinta®.Materials and methods. The subject of this research is API ticagrelor including air and flush samples from the surface of LLC «AstraZenica Industries», collected during the production of the consignment of Brilinta® (MNN – ticagrelor). Air samples of the working area were collected using air intake systems of type "IOM Sampler", using both personal and stationary systems. Flushing from the surface is done by template v printing using cotton swaps. Sampling points selected to cover. All stages of the production cycle. Subsequently, the quantification of ticagrelor in samples was carried out by the method of high-efficiency liquid chromatography with UV detection (HPLC-UV).Results and discussions. The quantitative determination showed that 4 air samples and 25 surface fluxes exceeding the allowable content of ticagrelor. Each sample was related to the time and place of sampling, and assumptions were made as to why the sample points exceeded the standard values.Conclusion. At the pharmaceutical enterprise we have carried out hygienic monitoring of the working area air for the content of API ticagrelor. The results of the measurements were obtained and processed, on the basis of which measures were proposed to reduce the concentration of ticagrelor in the air in order to protect personnel from the adverse effects of the work area. These measures include optimization of process operations and/or training of personnel in new approaches to the operation and cleaning of equipment.